Hi friends, I have a following equation : x = x^{2} - [(N-1) * 2], where N = 11 that becomes: x = x^{2} - (20) My question: If possible, how can we derive the value of x in the equation x = x^{2} - (20) ? Thanks in advance, Regards.
Follow Math Help Forum on Facebook and Google+
Originally Posted by bytelogik Hi friends, I have a following equation : x = x^{2} - [(N-1) * 2], where N = 11 that becomes: x = x^{2} - (20) My question: If possible, how can we derive the value of x in the equation x = x^{2} - (20) ? Thanks in advance, Regards. Write it as x^2 - x - 20 = 0 and then factorise or use the Quadratic Formula.
View Tag Cloud